Analysis of the tacit hypothec : section 118 of the Local Government : Municipal Systems Act 32 of 2000 in light of the CC’s judgment in Jordaan v City of Tshwane - Brits, Reghard (University of Pretoria, 2019)
Dissertation (LLB)-University of Pretoria, 2018.